Sustainability in marketing: a review using multiple correspondence analysis - Yating Tian; Qeis Kamran; Jörg Henseler (Cogent Business & Management)
This study examines the state of sustainability in leading marketing research and proposes a bottom-up framework that involves business managers, consumers and the environment at different levels. A qualitative approach involving multiple correspondence analysis is used to examine the status of sustainability in marketing, and a solution-oriented framework based on a bottom-up approach is designed. Three dimensions are determined to be at the heart of the consumer–business–society relationship: sustainable environmental awareness and responsibility, production and consumption practices, and intercompany and industrial collaborations. Based on these dimensions, a holistic framework is developed to address the conflicts between theory and practice toward sustainability values. This study refines the market-driven concept and guides scholars through our proposed path that unites marketing and sustainability. We also design a framework by incorporating social marketing elements into businesses to achieve sustainability. Ultimately, this study offers insights into consumer research, marketing management and sustainable business practices.